2015
DOI: 10.3389/fpls.2015.00669
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of a membrane-enriched fraction from flag leaves reveals responses to chemical hybridization agent SQ-1 in wheat

Abstract: The induction of wheat male fertile lines by using the chemical hybridizing agent SQ-1 (CHA-SQ-1) is an effective approach in the utilization of heterosis; however, the molecular basis of male fertility remains unknown. Wheat flag leaves are the initial receptors of CHA-SQ-1 and their membrane structure plays a vital role in response to CHA-SQ-1 stress. To investigate the response of wheat flag leaves to CHA-SQ-1 stress, we compared their quantitative proteomic profiles in the absence and presence of CHA-SQ-1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 71 publications
(82 reference statements)
0
29
0
Order By: Relevance
“…CHA SQ-1 can effectively induce male sterility in most wheat varieties, reaching rates of up to 95%. Meanwhile, the seed setting rate of artificial saturation pollination can reach 98% [16]. This result shows the great potential of utilizing heterosis.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…CHA SQ-1 can effectively induce male sterility in most wheat varieties, reaching rates of up to 95%. Meanwhile, the seed setting rate of artificial saturation pollination can reach 98% [16]. This result shows the great potential of utilizing heterosis.…”
Section: Discussionmentioning
confidence: 78%
“…Hence, it is urgently required to ameliorate the male sterility induced by SQ-1. Thereafter, we could improve the induction efficiency of male sterility to reduce this self-fertility.Therefore, several studies have investigated the molecular mechanism behind the sterility induced by SQ-1, including characterization of its physiological and biochemical metabolism characteristics [48,49] as well as the genes related to pollen grain development [19,24,50] and proteome [16,22,23,51] and epigenetic [52][53][54][55] profiles. However, the molecular mechanism underlying SQ-1-induced male sterility remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…China (34° 16’ N, 108° 4′ E). The following April when the wheat had reached a growth stage of 8.5 according to the Feekes scale (as described in [ 23 ]), wheat plants were divided into two groups, with 50 rows per group. While plants from one group were treated with the CHA SQ-1 (5 kg ha −1 ) and named PHYMS-1376, the other plants, which were sprayed with water as a control, were named MF-1376.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, more than applicable 40 CHAs have been reported ( Singh et al, 2015b ), some of which are found effective in inducing pollen sterility, such as RH007 ( Mizelle et al, 1989 ), SC2053 ( Fan et al, 1998 ), and Genesis ( Singh et al, 2010 ). Compared with them, SQ-1 is an ideal chemical hybridization agent which could induce male sterility by changing the cell microstructure ( Wang et al, 2016 ), triggering programmed cell death (PCD) ( Wang et al, 2015a , 2016 ), striking the oxidative/antioxidative balance ( Wang et al, 2016 ) and increasing the cell membrane permeability ( Song et al, 2015 ). Despite some progress toward understanding the mechanisms of male sterility has been made, such as reactive oxygen and aliphatic metabolism ( Ba et al, 2013 , 2014a ), DNA methylation ( Ba et al, 2014b ), cell morphological ( Wang et al, 2015a ), transcriptome ( Zhu et al, 2015 ) and proteomics ( Song et al, 2015 ; Wang et al, 2015b ), the mechanisms underlying male sterility in plants resulting from CHA treatment remain elusive.…”
Section: Introductionmentioning
confidence: 99%